Creative resistance: Noah Baumbach's literary filmography. Issue 10 (3rd October 2021) - Wilkins, Kim
ABSTRACT: It is frequently asserted in both film scholarship and criticism that Noah Baumbach is a literary filmmaker. While Baumbach's oeuvre certainly showcases his interest in literature through a range of stylistic techniques, this article presents the case that Baumbach projects his literary filmmaking as an authorial trademark in line with Timothy Corrigan's conceptualisation of contemporary auteurism. By critically positioning himself as an auteur, Baumbach seemingly defies insurgent pushes toward broad discourses of neoliberal creativity and attendant preoccupations with entrepreneurialism, adaptability, and flexibility. This strategy resonates with the narratives presented in Baumbach's films, which overwhelmingly centre on the plights of medium-specific artists in crisis. As such, at first glance, Baumbach's auteurist positioning and his narrative and thematic preoccupation with artists unfulfilled by the promises of the creative class could be read as resistance to neoliberal creativity per se . Yet, as an auteur within the highly marketable American indie tradition, Baumbach's literary filmmaking ultimately facilitates his participation in the neoliberal creative practices that his discursive auteurist positioning and film narratives appear to resist.